Structural assessment and remedial planning for a concrete slab bridge: A case study - Maria Rashidi; Mohammad Siahkouhi; Krishna Shrestha; Mohammad Sadegh Ayubirad; Mahyar Jafarkazemi (Results in Engineering)
Aging transportation infrastructure, particularly bridges exceeding their intended service lives, presents significant safety and economic challenges worldwide. This study addresses this critical issue by developing and validating a comprehensive methodology for strengthening deteriorating steel-concrete composite bridges using Carbon Fiber-Reinforced Polymer (CFRP) systems. The main contribution of this work lies in its integrated approach, which seamlessly combines detailed structural assessment (using finite element modeling rigorously validated against field measurements from the Riverside bridge case study), optimized CFRP strengthening design (based on parametric analysis applied to the Gross bridge, a 62-meter structure), and practical implementation protocols. The finite element model demonstrated high accuracy, with predictions varying by <6 % compared to field measurements. Structural analysis highlighted the criticality of multi-vehicle loading scenarios, showing a 69.1 % increase in stress levels (reaching 35 MPa) at 100 km/hr compared to single-vehicle loading. Parametric studies on CFRP thickness (1.5 mm, 2.5 mm, 3.5 mm) informed the optimization, indicating that the 3.5 mm configuration offered a slight load-bearing advantage (approx. 5 % more load for 2.48 mm deflection under 35 kN static load) over the 2.5 mm thickness. A Simplified Analytical Hierarchy Process, incorporating safety, cost, and environmental factors, evaluated rehabilitation options and confirmed CFRP strengthening as the optimal strategy (scoring 387.5). Ultimately, this research establishes a robust, validated framework that provides engineers and asset managers with a practical and reliable tool for extending bridge service life while meeting safety requirements. This integrated methodology enhances decision-making for bridge rehabilitation and is adaptable for similar composite bridge structures, representing a promising advancement in sustainable infrastructure maintenance practices.